BLOOD SMEAR EXAMINATION AND DIFFERENTIAL COUNT IN RATS WITH ESCHERICHIA COLI ESBL AND KLEBSIELLA PNEUMONIAE CARBAPENEMASE INFECTIONS - Savitri, Lisa; Kasimo, Elfred Rinaldo; Ihsan, Kharisul; Faizal, Imam Agus (BRIN - Badan Riset dan Inovasi Nasional, 2025)
Sepsis is an irregular body response to severe infection, triggering uncontrolled inflammation that can lead to extensive tissue damage. It can progress to septic shock with multiple organ failure, resulting in death if left untreated. Laboratory examinations, such as leukocyte differential count in hematology, help understand the distribution pattern of white blood cells associated with health conditions. Laboratory research was conducted on mice injected with E. coli ESBL or K. pneumoniae carbapenemase. After 24 hours, observations were made on apoptosis in the spleen and liver of mice. Mouse blood was processed to count white blood cell types with a differential count. The results were analyzed to compare the control group with the bacterial infection groups of E. coli ESBL and K. pneumoniae carbapenemase. The research results indicate that the neutrophil count in the E. coli ESBL group is still within the normal range and lower (44.5±1.915%) compared to the K. pneumoniae carbapenemase group (55.75±8.342%). Similarly, the lymphocyte count in the E. coli ESBL group is within the normal range and lower (77.5±3.109%) compared to the K. pneumoniae carbapenemase group (91.25±7.588%). This highlights the crucial role of neutrophils and lymphocytes in responding to severe bacterial infections such as K. pneumoniae carbapenemase. Previous studies indicate neutrophilia and lymphocytopenia as markers of severe bacterial infections. Neutrophils are the primary defense against bacterial infections and can be rapidly recruited to the infection site, while specific infections can trigger prolonged neutrophil recruitment from hematopoietic tissues.